Corporate Criminal Liability for Criminal Acts of Corruption: A Comparison of State Criminal Law Systems and Civil Law Systems - Seri Karna, Kadek Yoga Maheswara; M.E. Purwani, Sagung Putri (Westscience Press, 2025)
This study examines corporate criminal liability in corruption cases within the civil law system, comparing the legal frameworks of Indonesia and France. The civil law system, adopted by both countries, relies on codified laws rather than judicial precedents. In Indonesia, corporate liability for corruption is regulated under Law No. 31 of 1999, as amended by Law No. 20 of 2001, while in France, it is governed by the French Penal Code (Code Pénal Français). Findings show that neither country provides a single explicit provision detailing which corruption offenses corporations can commit, requiring semiotic and systematic interpretations to determine applicable liability. In France, corporations may be held liable for active and passive bribery, influence peddling, unlawful benefit-taking, and favoritism in procurement, as stipulated in Articles 433-1, 435-1, 432-11, 432-12, and 432-14 of the Code Pénal Français. Similarly, Indonesia allows corporate liability for bribery, misuse of authority, unlawful enrichment, obstruction of justice, and related offenses, though certain crimes involving personal duties such as abuse of office remain limited to natural persons. Despite regulatory differences, both systems emphasize that only offenses feasibly committed by corporations may incur liability, highlighting the need for clearer procedural guidelines and legal harmonization.